SOME RELATIONS BETWEEN THE μ-PARAMETERS OF REGULAR GRAPHS - Davtyan, N.N.; Kamalian, R.R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
We consider undirected, simple, finite, connected graphs. Some relations between the μ-parameters are obtained for the case of regular graphs.